Neuroprotective effect of South Sulawesi propolis on neurogenesis in primary cultures of rat cerebral cortical neurons - Nurhadi Ibrahim; Trinovita Andraini; Amirah Yusnidar; Putu Indah Paramita Adi Putri; Imelda Rosalyn Sianipar (Universa Medicina, 2023)
BackgroundNeurodegenerative diseases have a significant risk factor, namely aging, which is associated with increased neuronal dysfunction and death. Propolis has been widely used as medicine due to its various benefits. This research study investigated the effect of propolis from the stingless bee (Tetragonula sapiens) from South Sulawesi, Indonesia, on neurogenesis in primary cultures of embryonic cerebral cortex of Wistar rats at 17-18 days of gestation. Methods This research was an experimental study involving 4 female pregnant Wistar rats, which were terminated and the cerebral cortex of the embryos collected and grown as primary cultures. The cultures were divided into 3 groups, i.e. control, vehicle, and propolis extract group. The research began with 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) to obtain the optimal dose among propolis doses of 0.5 μg/mL, 1 μg/mL, 5 μg/mL, 10 μg/mL, 25 μg/mL, and 100 μg/mL. The study was continued by using the best dose in immunostaining examination using microtubule-associated protein 2 (MAP2) primary antibody and qRT-PCR examination of brain-derived neurotrophic factor (BDNF) mRNA expression. One Way ANOVA and Kruskal-Wallis test were used to analyse the data. ResultsThe results showed that the propolis doses of 0.5 μg/mL and 1 μg/mL significantly increase cell viability compared to the other doses (p=0.011) and stimulate dendritic growth. The propolis dose group of 1 μg/mL induces a significantly higher expression of BDNF mRNA than the control group (p=0.031). ConclusionOur findings indicate that stingless bee propolis has neuroprotective effects against BDNF mRNA in rats. It is shown that propolis can be a candidate inhibitor in neurodegenerative diseases.